2006
DOI: 10.4049/jimmunol.177.12.8612
|View full text |Cite
|
Sign up to set email alerts
|

Differential IFN-γ Stimulation of HLA-A Gene Expression through CRM-1-Dependent Nuclear RNA Export

Abstract: IFNs regulate most MHC class I genes by stimulating transcription initiation. As shown previously, IFN-γ controls HLA-A expression primarily at the posttranscriptional level. We have defined two 8-base sequences in a 39-nucleotide region in the 3′-transcribed region of the HLA-A gene that are required for the posttranscriptional response to IFN-γ. Stimulation of HLA-A expression by IFN-γ requires nuclear export of HLA-A mRNA by chromosome maintenance region 1 (CRM-1). Treatment of cells with leptomycin B, a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 60 publications
(64 reference statements)
2
12
0
Order By: Relevance
“…3’UTRs encode docking sites for miRNAs (10, 11) as well as RBPs(8, 9), which are the major determinants of post-transcriptional gene regulation. Several reports indicate a role of 3’UTR associated RBPs in the post-transcriptional regulation of HLA genes (1417), including another member of the heterogeneous nuclear ribonucleoprotein family, HNRNP-R (17). We identified the RBP Syncrip as the translational inhibitor of the long form of the HLA-A 3’UTR.…”
Section: Discussionmentioning
confidence: 99%
“…3’UTRs encode docking sites for miRNAs (10, 11) as well as RBPs(8, 9), which are the major determinants of post-transcriptional gene regulation. Several reports indicate a role of 3’UTR associated RBPs in the post-transcriptional regulation of HLA genes (1417), including another member of the heterogeneous nuclear ribonucleoprotein family, HNRNP-R (17). We identified the RBP Syncrip as the translational inhibitor of the long form of the HLA-A 3’UTR.…”
Section: Discussionmentioning
confidence: 99%
“…If DDX3 was needed for the export of snRNA via CRM1 it could indirectly have an effect on splicing by affecting the maturation of snRNAs, which are exported from and re-imported into the nucleus before they assemble with other splicing factors into a functional spliceosome [22]. Also, a small subset of inducible mRNAs, including IFN mRNA and IFN -induced HLA-A mRNA [23,24] is exported by CRM1 rather than TAP. Given its recently identified role in anti-viral gene expression [9] (further discussed in sections 3.5 and 5.1), it is tempting to speculate that DDX3 might have a role in mediating the export of these and other immuno-relevant mRNAs.…”
Section: Nuclear Export Of Rnamentioning
confidence: 99%
“…FLAG-tagged CIITA, GFP-tagged PRMT1, HA-tagged PRMT1 (WT and EQ), PRMT1 short hairpin RNA (shRNA) plasmid, DRA300 reporter have been previously described67141516. Small interfering RNA (siRNA) for mouse and human PRMT1 was purchased from Dharmacon.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Browne et al . have shown that PRMT1 inhibition attenuates the expression of HLA-A, but curiously not HLA-E, by IFN-γ in cancer cells15. PRMT1 has also been shown to repress NF-κB-mediated inflammation by methylating and preventing RelA from binding to target genes16.…”
mentioning
confidence: 99%